ANTIMICROBIAL EXAMINATIONS OF CYMBOPOGON CITRATUS AND ADIATUM CAPILLUS-VENERIS USED IN GHANAIAN FOLKLORIC MEDICINE: Life Science-Chemistry - NYARKO, HUBERT D.; BARKU, VICTOR Y. A.; BATAMA, JOSEPH (International Journal of Life Science and Pharma Research, 2012)
The antimicrobial activity and Minimal Inhibitory Concentration (MIC) of the extracts of Cymbopogon citratus and Adiatum capillus-veneris were evaluated against four bacteria (Staphylococcus aureus, Proteus mirabilis, Klebsiella pneumonia, Pseudomonas aeruginosa, and a fungus (Candida albicans). These plants are used in Ghanaian folk medicine to treat infections of microbial origin. The antibacterial and antifungal activities were tested using agar diffusion technique. The ethanol extracts of the two plants showed appreciable antimicrobial and antifungal activity against Staphylococcus aureus, Proteus mirabilis, Klebsiella pneumonia and Candida albicans with MIC of 0.78mg/ml and 12.5mg/ml for C. citratus and A. capillus-veneris respectively. However, the aqueous extract of Cymbopogon citratus showed no activity against the tested organs but that of Adiatum capillus-Veneris had activity against Proteus mirabilis and Klebsiella pneumonia. All the plants show different kinds of phytochemicals. The phytochemical investigation revealed the presence of sugars, flavanoids, triterpenoids, and steroids for A. capillus-veneris and flavonoids, anthraquinones, alkaloids, saponins, phenols and steroids for C.citratus. Statistical analysis using student t-test showed no statistical difference between MICs of the two plants and chloramphenicol.